Comparative evaluation of flexural strength of denture base resin materials processed using compression molding technique, injection molding technique, and computer-aided design CAM technique: An in vitro study - Rutika C Patankar; Vijaysinh More; Rajashree Jadhav; Ajay Sabane; Pankaj Kadam; Arti Gachake (Wolters Kluwer Medknow Publications, 2022)
Background: Denture bases undergo repeated flexing during mastication leading to fatigue failure, demanding a high fatigue strength property. Flexural (transverse) strength is required high to prevent catastrophic failure under load for success. Denture base resins are fabricated by three different types of manufacturing: Compression molding, injection molding and computer-aided design (CAD/CAM) milling technique. The study was conducted to identify the denture with the highest flexural strength (Fs) from these methods. Materials and Methods: In this in vitro study. Three groups of 15 PMMA acrylic denture base resins (total 45) were processed into rectangular plates of size 65mm × 10mm × 3mm. The three groups differed in the method of processing as compression molded, injection molded, and prepolymerized CAD/CAM milled resins. A 3-point bend test was used to measure the Fs. One-way analysis of variance (ANOVA) with the Post hoc Tukey method was used for statistical analysis. Data was statistically significant with Post hoc Tukey method significance at P < 0.05. Results: The mean Fs of CAD/CAM, injection molding, and compression molding manufacturing techniques are 97.46, 84.42, and 71.72 respectively and standard deviation obtained are 9.93, 10.42, and 11.58, respectively. Statistical analysis suggested the CAD/CAM technique as the best method for the fabrication of dentures because it had the maximum mean Fs and the lowest Fs standard deviation when compared with compression molding and injection molding. Conclusion: Denture bases fabricated through CAD/CAM technique are more sustainable than the compression-molded and injection-molded denture bases.